2012
DOI: 10.1111/j.1471-3802.2011.01230.x
|View full text |Cite
|
Sign up to set email alerts
|

Technology for people, not disabilities: ensuring access and inclusion

Abstract: The potential of technology to connect people and provide access to education, commerce, employment and entertainment has never been greater or more rapidly changing. Communication technologies and new media promise to ‘revolutionize our lives’ by breaking down barriers and expanding access for disabled people. Yet, it is also true that technology can create unexpected and under‐critiqued forms of social exclusion for disabled people. In addition to exploring some of the ways that even (or especially) assistiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(103 citation statements)
references
References 9 publications
2
98
1
2
Order By: Relevance
“…Limited accessibility to available resources for rehabilitation or assistance technologies would slow down their adoption, this finding is congruent with a study by Hughes et al [28] which concluded that the lack of information and access to assistive devices as the main reasons for not using them. Funding availability is another factor limiting the accessibility of upper extremity assistive devices, also, this finding is congruent with Demain's study [33] stating that the lack of funding for upper limb assistive technologies hampered their development.…”
Section: Theme 3: Bumps On the Roadsupporting
confidence: 81%
See 1 more Smart Citation
“…Limited accessibility to available resources for rehabilitation or assistance technologies would slow down their adoption, this finding is congruent with a study by Hughes et al [28] which concluded that the lack of information and access to assistive devices as the main reasons for not using them. Funding availability is another factor limiting the accessibility of upper extremity assistive devices, also, this finding is congruent with Demain's study [33] stating that the lack of funding for upper limb assistive technologies hampered their development.…”
Section: Theme 3: Bumps On the Roadsupporting
confidence: 81%
“…Research done by Portacolone [32] and Foley [33] found that there is a profound tension regarding what is considered independence, still in our study, stroke participants considered depending on assistive devices would be a stigma. This finding is congruent with previous research done by Silvers [34], where the authors concluded that persons of any age can feel stigmatized by devices that signal loss of function.…”
Section: Theme 1: "They Exist But…"contrasting
confidence: 53%
“…Common to them all, however, is the concept of an item or piece of equipment that enables individuals with disabilities to enjoy full inclusion and integration in society 37,72,88 . Traditional assistive technologies include white canes, screen readers, walkers, etc.…”
Section: Assistive Technology: Goals and Interpretationsmentioning
confidence: 99%
“…The modified version could allow the participants to use mini objects or pictures (i.e., rather than verbal utterances) as means to request/access specific leisure or communication activities (Buchholz et al 2013;Foley and Ferri 2012). The objects or pictures could be supplied with special frequency code labels that make them recognizable by a smartphone (Ricci et al 2017).…”
Section: Introductionmentioning
confidence: 99%